Analysis of Smart Home Systems in the Context of the Internet of Things in Terms of Consumer Experience - Türkyılmaz, Serap; Altindag, Erkut (International Review of Management and Marketing, 2022)
Smart homes, which are an important component of the Internet of Things (IoT) provides an effective service for users by communicating with various digital devices based on IoT. IoT-based smart home technology has transformed the lives of humans by providing everyone with a connection independently from time and space. However, due to various challenges such as privacy, security, and price, problems are experienced by consumers in terms of accepting smart home technologies. In the study, it was aimed to develop a model for accepting smart home technologies, and based on the results obtained, it was attempted to determine what factors affect the consumers’ intention to buy smart home systems. In this context, with the help of Technology Acceptance Model (TAM), a research model was designed for the purchaser of a home as a product. In the research model, it was investigated what kind of effects perceived psychological factors (perceived ease of use, perceived intelligence, perceived suitability, perceived price, and perceived risk of privacy) have on the purpose and behavior of using IoT systems through perceived benefit. In addition, the relationship between sensory and emotional experiences of consumers, psychological perception factors and perceived usefulness was tested. Data was collected by conducting an online survey questionnaire completed by 430 respondents. Partial least squares (PLSs) was explored to test the theoretical model. The research results show that perceived psychological factors (perceived ease of use, perceived connectivity, perceived intelligence, perceived convenience, and perceived privacy risk) have significant effect on the intention and behavior of IOT systems usage through perceived benefit. In terms of sensory and emotional experience, it only softens the relationship between the perceived privacy risk of emotional experience and the perceived benefit.